Visual genetics plus - Day, Alan W.; Dean, Robert L. (Sudbury, MA Exeter Multimedia Pub., 1998)
Contents: DNA structure and heredity/ Mendelian genetics/ Chromosomal basis of heredity/ Gene linkage and chromosome mapping/ Variation in chromosome number structure/ Structure and replication of DNA/ Genetics of bacteria and viruses/ Gene expression/ Genetic enguineering and genome analysis/ Regukation of gene activity/ Genetic control of development/ Mutation, DNA repair and recombination/ Population genetics/ Genetics of complex multifactorial traits/ cell biology
Title from disc label.
System requirements: McIntosh- A 16Mhz 68020 or better processor, 6 MB RAM minimum, System 6.07 or higher, color monitor, and a cd-ROM drive. Windows- A 386 or better processor, with at least 4 MB RAM minimum, Microsoft Windows 3.11 or higher, color VGA monitor and a CD-ROM drive.
Keywords: Genetics -- Computer simulation; Genetics -- Examinations, questions, etc